ASEAN and the Belt and Road Initiative: Trust-building in trade and investment - HSU, Locknie (Institutional Knowledge at Singapore Management University, 2020)
This article examines a number of trade and investment areas in which trust-building needs to occur between China and its ASEAN Belt and Road Initiative partners in order to better realize the economic benefits promised by the initiative. A number of economic goals of ASEAN converge with those of the BRI, such as those relating to building physical, regulatory and digital connectivity, and this convergence provides potential for joint economic growth and cooperation. Some of ASEAN’s urgent infrastructure needs, for instance, could be met through ASEAN-BRI collaboration. However, a number of issues which have arisen in BRI-related projects within and outside ASEAN need to be addressed in a convincing way, if ASEAN and China are to better achieve such economic goals. These include building trust by fostering confidence that the BRI brings domestic trade and investment benefits, good governance and financial and environmental sustainability, and in the newer field of digital connectivity, by ensuring meaningful dialogs and actions on the use of existing and emerging technology in the BRI.